Increased coronary artery disease severity in patients undergoing invasive diagnostics during the COVID-19 pandemic - Tomasz Wcisło; Karolina Kołodziej; Marcin Książczyk; Kasper Kuna; Damian Mikulski; Ewa Borowiak; Michał Plewka (Nofer Institute of Occupational Medicine, 2024)
Background This study aimed to compare the stage of coronary heart disease in patients who underwent invasive cardiac diagnostics during the COVID-19 pandemic and before, based on the number of medical devices used and the number of complex coronary angioplasty procedures performed. Material and Methods A retrospective, single-center study was conducted, which included 187 successive patients with diagnosed coronary heart disease, who were divided into 2 groups: group I (N = 92, pre-COVID-19 pandemic) and group II (N = 95, during COVID-19 pandemic). Results Despite a comparable number of invasive procedures in both groups, stent length and contrast use per procedure were significantly higher during the COVID-19 pandemic. Similarly, a higher number of stents was used per patient in 2021, however, the difference was not statistically significant (p = 0.0817). Similarly, fluoroscopy time per procedure and procedure duration were significantly longer in the 2021 group. Among patients treated during the COVID-19 pandemic, higher glucose concentration, blood pressure parameters, low-density lipoprotein and total cholesterol were observed; however, these differences were not statistically significant. Conclusions During the COVID-19 pandemic, coronary atherosclerosis progression were found, requiring a higher number of complex coronary angioplasty procedures, which contributed to a statistically significant increase in the number of medical devices used (angioplasty guidewires, angioplasty balloons) and procedures duration. Med Pr Work Health Saf. 2024;75(4):333-342